1685 Mood Disorders in Postpartum Period at a Rural Teaching Hospital in Western India. (October 2012) - Nimbalkar, SM; Nimbalkar, AS; Patel, H; Chaudhary, NS; Gadhavi, KV; Ganjiwale, JD; Vasa, R; Vani, SN
Abstract : Background and Aims: Post Partum Blues/Mood Disorders affects 50–80% of women in the first two weeks Post partum. Post partum depression affects 10% of women and post partum psychosis affects 1/1000 women. Methods: Determine ease and feasibility of EPDS in State of Gujarat, India. Determine incidence of post partum mood disorders/blues in Anand district, Gujarat. Women delivering beyond 30 weeks at Shri Krishna Hospital, Karamsad were asked to complete EPDS survey within a week of Delivery (after informed consent). The EPDS form was translated in Gujarati language. The study was conducted for one month. EPDS score of 10.5 or more was considered high risk. Results: The prevalence of post partum blues was 48.5%. Factors associated with post partum blues were birth weight, difficulty in breastfeeding, mother's worries about the infant and whether pregnancy unwanted. 90% of the women with unwanted pregnancy had mood disorder. Addiction of husband and violence from husband were also associated to the mood disorder of the new mother. Infant death was not found to be associated with mood disorder in mothers as mothers with infants surviving as well were proportionately found to have mood disorder. Gender of child did not show any association with the post partum blues in the mother. Conclusion: Post partum blues has a higher prevalence of 49% in our region. In India we need to study both the immediate post partum blues and post partum depression to understand their effects on child health.